Experimental study of carriageway operational condition influence on acoustic roadside area pollution - Ugnenko, Evgenija; Gavrish, Vadim; Viselga, Gintas; Garbinčius, Giedrius; Turla, Vytautas; Nagurnas, Saulius (Transport, 2019)
Environmental noise management is an important part of the policy across the EU policy context, because transportation noise is a significant local environmental problem for most of the urban population. Increasing numbers of vehicles are associated with growing noise levels from road transport in urban areas and rising public health problems. Motor transport is considered to be a main source of noise pollution, so it is important to investigate the level of traffic noise and assess the relationship with traffic flows. The paper describes the main methods for determination of noise characteristics of traffic flows. The dependences for the prediction of the equivalent noise level and the results of field measurements of sound levels are presented. The results of field experiments and the calculated values of sound levels obtained by the analytical method are tested for homogeneity, using the Wilcoxon test. Experimental studies have established that the external sound level depends largely on the speed of vehicles, road conditions, and basic operating characteristics of highways. The analytical method associated with the use of deterministic and probabilistic models makes it possible to predict the traffic noise. But when dealing with the foregoing methods, there arise specific problems, many of which have not been resolved: there is no uniform terminology, nor is there any consensus on the use of noise characteristics of traffic flows in calculations at different stages of construction and reconstruction of highways of a certain traffic flow model under conditions of human settlements. Standardized measurement methods have been established and revised throughout the years by many renowned researchers. These methodologies have been revised in order to minimize problems that may occur and may not be foreseen by a less experienced researcher when adopting the measurement methods. Standardizing the measurement method is also useful for researchers because it becomes possible for researchers from around the world to compare their data. The joint effect of road conditions and the operational status of the roadway on the acoustic pollution of the roadside area is not fully taken into account. Therefore, applying the internationally recognized acoustical measurement standards is a good way to start any noise measurement experiment. The purpose of experimental research is to investigate the joint effect of road conditions and the operational status of the roadway on the acoustic pollution of the roadside area of settlements: identify the main characteristics of noise produced by traffic flows, consider the comparability of results of the field experiment and analytical computations. Slopes of 20…40‰ have little impact on the noise caused by the movement of passenger cars and trucks. In this case, the average acoustic emissions are identical to those used in the prediction of noise mode.